"A Different Story to Share": Asian American English Teachers in Taiwan and Idealized "Nativeness" in EFL. Issue 1 (2nd January 2022) - Wu, Ming-Hsuan; Leung, Genevieve; Yang, Jhih-Kai; Hsieh, Ivy Haoyin; Lin, Kelly
ABSTRACT: In a broader context where English is marketed as a desirable product of consumption, hiring English speakers as language teachers and de facto cultural ambassadors is a common practice in some East Asian countries. This paper investigates how 20 self-identified Asian American teachers in Taiwan teaching English in local schools wrestle with the positionality of their racialized selves and idealized "nativeness." Using an informal interview approach, a grounded theory framework, and narrative analysis, we investigated how participants made sense of their Asian American-ness in the ELT profession in Taiwan. Findings include complex feelings involving the image of Asian Americans, strategic language use to construct Asian-American-in-Taiwan identities, and unique interpretations of teaching U.S. culture. We discuss the emotional labor and strategic discourses these teachers undertook to convert their cultural and linguistic capital and offer suggestions for professional and curriculum development.